Lubrication Characteristics of a Warhead-Type Irregular Symmetric Texture on the Stator Rubber Surfaces of Screw Pumps - Xinfu Liu; Yi Sun; Chunhua Liu; Xiangzhi Shi; Xinglong Niu; Gang Zheng; Wei Wei; Songbo Wei; Shouzhi Huang (Lubricants)
A theoretical model for the micro-texture on the inner wall of the stator rubber in screw pumps was developed. The finite element analysis method was employed. The pressure and streamline distributions for warhead-type, concentric circle-type, and multilayer rectangular-type textured surfaces were calculated. The effects of textured morphology, groove depth, groove width, and other parameters on the lubrication field were systematically investigated and analyzed. A nanosecond laser was employed to process the textured rubber surface of the stator in the screw pump. Subsequently, a micro-texture friction performance test was conducted on the rubber surface of the stator in actual complex well fluids from shale oil wells. Given the results of the simulation analysis and experimental tests, the lubrication characteristics of textured rubber surfaces with varying texture morphologies, rotational speeds, and mating loads were revealed. Furthermore, it indicated that the irregular symmetric warhead-type micro-texture exhibited excellent dynamic pressure lubrication performance compared with concentric circle-type and multilayer rectangular-type textures. The irregular symmetry enhanced the dynamic pressure lubrication effect, enhanced the additional net load-bearing capacity of the oil film surface, and reduced friction. As the groove depth increased, the volume and number of vortices within the groove also increased. The fluid kinetic energy was transformed into vortex energy, leading to a reduction in wall stress on the surface of the oil film, thereby affecting its bearing capacity. Initially, the maximum pressure on the wall surface of the oil film increased and then decreased. The optimal dynamic pressure lubrication effect was achieved with a warhead-type texture size of 3 mm, a groove width of 0.2 mm, and a groove depth of 0.1 mm. Well-designed texture morphology and depth parameters significantly enhanced the oil film-bearing capacity of the stator rubber surface, improving the dynamic pressure lubrication effect, and consequently extending the service life of the stator–rotor interface in the screw pump.